„Chrześcijańska joga”? Słów kilka o modlitwie Jezusowej i hezychazmie - Brzeziński, Bartłomiej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The article “«Christian yoga»? A few reflections on the Jesus’ Prayer and hesychasm” is a kind of commentary on the Polish translation of the article “Becoming what we pray...” by Michel Plekon that is presented in the same issue of periodical “Kultury Wschodniosłowiańskie — oblicza i dialog”. Author tried to remind the most important facts and figures connected with the history of the Jesus’ Prayer and hesychasm. Moreover, there are described controversies concerning the physical method that was used by some hesychasts during practice of the Jesus’ Prayer. Additionally, one can readabout the role of the heart in Orthodox theology and prayer tradition of Eastern Church. This role can not be overtaxed because from the point of view of Orthodox theology, the heart is the centre of human being, person. It is not only the physical organ, not only the area of emotions and affections but also the space of intelligence, thoughts and wisdom. But most of all, the heart is the place of mysterious meeting of God and man. In the secret hall of human heart a man can fell silent presence of Transcendence, can fellthe real epiphany of God who unceasingly waits for metamorphosis of human being’smentality, thinking, reason, activity, emotions, relations, who waits for transformation of the whole man.